초기 외상성 앞방출혈에서 초음파생체현미경의 임상적 의의 - 장동호; Dong Ho Chang; 이평; Pyung Lee; 이승찬; Seung Chan Lee; 진경현; Kyung Hyun Jin (Daihan angwa haghoi jabji, 2010)
목적: 초기 외상성 앞방출혈에서 초음파생체현미경을 이용한 양안 앞방각간 거리 계측의 임상적 의의를 알아 보고자 하였다. 대상과 방법: 외상성 앞방출혈로 입원한 46명을 대상으로 입원 초기 앞방출혈의 양을 조사하고, 초음파생체현미경을 통한 앞방각 후퇴범위, 앞방각간 거리(AOD500)를 측정하여 이들 간의 관련성을 알아보고자 하였다. 결과: 외상성 앞방출혈 환자에서 입원 시 실시한 초음파생체현미경상의 앞방각 후퇴의 범위가 넓은 군에서 수상안과 건안 간의 앞방각 간 거리의 차가 유의하게 컸다(p=0.008). 입원 초기 앞방출혈의 양이 많은 군에서 수상안과 건안 간의 앞방각간 거리의 차가 더 컸으나 유의성을 보이지는 않았다. 결론: 외상성 앞방출혈 환자에서 혈병이 있는 초기에 초음파생체현미경을 이용하여 양안 앞방각간 거리를 측정하면 앞방각 후퇴의 범위를 추측해 볼 수 있을 것이다. <대한안과학회지 2010;51(1):106-111> Purpose: To evaluate the clinical significance of angle-opening distance 500 (AOD500) using ultrasound biomicroscopy (UBM) in the early stage of traumatic hyphema. Methods: The participants of this study were 46 hospitalized traumatic hyphema patients. We measured the quantity of initial blood clotting using a slit-lamp and the range of angle recession, AOD500 using UBM and then reviewed the relationship between the two. Results: The difference of AOD500 in the traumatic and the non-traumatic eye measured by UBM at admission increased significantly in the wider recessed angle group (p=0.008), but did not increase at a statistically significantly level in the larger initial blood clot grade group (≥Grade 2). Conclusions: These results suggest that the measurement of the angle-opening distance of both eyes using UBM will aid in evaluating the range of angle recession in patients in the early stage of traumatic hyphema. J Korean Ophthalmol Soc 2010;51(1):106-111